Combining ability and heterosis studies for oil and seed meal quality traits in Indian mustard (Brassica juncea L.) (Journal of Oilseed Brassica, 2026)
The study of combining ability, and heterosis for oil and seed meal quality traits in 40 F1s of Indian mustard, developed from 8 lines, and 5 testers was carried out in randomized block design with two replications at Crop Research Centre of Birsa Agricultural University, Ranchi, India during Rabi 2014-15. Analysis of variance revealed, significant differences among genotypes for all the traits. Higher gca variance indicated the role of additive gene action in inheritance of these traits except saturated fatty acid, and linolenic acid. The parents, Shivani and Heera were good combiner for most of the quality traits. Estimation of specific combining ability effects of crosses viz., NRCHB 101 x Heera, Pusa Bold x Pusa Mustard-21, Shivani x Heera, Pusa Mustard-25 x RGN-73, and BAUSM 92-1-1 x Pusa Mustard-21 were highly significant for glucosinolate content, erucic acid, oleic acid, and linoleic acid. Considering mean performance, and general combining ability effect, the parent, Heera was found promising for glucosinolate content, linoleic acid, and erucic acid. On the basis of mean performance, specific combining ability effect, and heterobeltiosis, the crosses, BAUSM 92-1-1x Pusa Mustard-21 for linoleic acid, and erucic acid, Shivani x BPR 543-2 for saturated fatty acid, NRCDR-02 x RGN-73 for linolenic acid, and NRCDR-02 x Heera for glucosinolate content were found promising. The cross, Shivani x Heera was found to be most promising showing desirability for maximum number of quality traits. Selection in early segregating generation is suggested to be more effective for breeding for quality traits in Indian mustard as most of them were found to be controlled by additive genes action.